STRATEGI PENGEMBANGAN PROGRAM PADAT KARYA TUNAI DESA (PKTD) DENGAN PENDEKATAN ANALISIS SWOT DI DESA STOWE BRANG KECAMATAN UTAN - Nurjihadi, M. (Jurnal TAMBORA, 2020)
This research was motivated by the implementation of the Village Cash Workforce Program(PKTD) As a priority program for the use of village funds in 2018 in Stowe villageBrang, Utan District, as one of the villages that has become a pilot project implementationPKTD program that has not been going well. This research aims toknow the strategic strategies for developing the Village Cash Workforce Program (PKTD),to find out what obstacles in the PKTD program and to find outefforts to overcome obstacles in the implementation of the PKTD program in Stowe VillageBerang, Utan District. This study uses a theory based onthe SWOT analysis presented by Siagian in determining Strategic Alternative.This study uses interviews, observation and documentation. Data analysisused is the Miles & Hubberman model. The result of the research is that the strategyappropriate to implement the Village Cash Workforce Program (PKTD) in the village of Stoweberang kecamatan utan is a strategy to use village funds for improvementcommunity capacity so that they have competence, strategies for the use of village funds andprofessional assistants in providing socialization to the community, andstrategies to increase coordination or cooperation between village governments, implementersactivities and society.